Kajian Semiotika dalam isi Kandungan Arti dan Makna Sebuah Lagu Satru ciptaan Denny caknan - Putri, Shinta Widyanti; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2021)
The purpose of writing this paper is to fulfill writing lectures and find out what language it is, various kinds of languages that can be used in song lyrics, several languages that will be pleasant to hear and make a beautiful rhythm. And can describe a Javanese song entitled Satru created by Denny Caknan. As a creator, Denny is very experienced and has a high imagination in creating a song that can be popular among the people and the song is a duet song with Happy Asmara who is none other than his former lover. The song is a sad song that describes a person who is jealous of his partner's behavior. From this story, it deserves to be popular, especially among teenagers who are falling in love and the pain of a broken heart. The method used to reveal the meaning and content in this song is descriptive qualitative. Research data in the form of words, sentences, and quotes in the song. The study used is Semiotics which focuses on the meaning in a song. The results of this study are containing various meanings in geguritan which have several meanings but make this song as its own characteristic in it.Â